Electric potential function of oblique current in laminated carbon fiber reinforced polymer composite beam. (15th July 2016) - Yamane, Takuya; Todoroki, Akira
Abstract: Orthotropic electric potential function analysis has shown to be applicable to the calculation of electric current density in laminated carbon composites. In our previous study, the analysis was limited to cases in which the electric current flows near the surface of the laminate. In some cases, the electric current flows in the through-thickness direction. When electric current flows in the thickness direction, the electric potential difference is completely different from that observed in the previous case. This study presents the new development of oblique flow potential analysis. The results of the analysis are verified by comparison with the results of FEM analysis and experimental measurements. Beam-type specimens containing two stacking sequences are used. The results indicate that the use of equivalent conductivity is effective for oblique electric flow. The experimental results show that the carbon fiber reinforced composites can be treated as a homogeneous material even for oblique electric current.